PERAMALAN TIME SERIES MENGGUNAKAN ANSAMBEL JARINGAN SYARAF - , IMELDA SALUZA ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Neural network is one method that is often used to predict time series data. In fact predicted by using neural network often occurs overfitting that causes the forecast is not good if used on different data. To overcome these problem, is used neural network ensemble method.